I gränslandet mellan svenskt och samiskt : Identitetsdiskurser och förhistorien i Norrland från 1870-tal till 2000-tal - Hagström Yamamoto, Sara (Uppsala universitet, Arkeologi, 2010)
The thesis studies the representation of prehistory as a part of the making and remaking of ethnic identities in Northern Sweden from the end of the 19th Century until today, thus dealing with archaeology and prehistory in relation to issues such as identity, memory and politics. The thesis takes as its point of departure the constitution of a Swedish national identity and memory in the late 19th Century and subsequent decades, followed by studies of, mainly later, representations of Sámi, Kvenish (“Kvänsk”) and North Bothnian (“Norrbottnisk”) collective identities. The study material consists of texts, primarily analyzed through discourse and narrative analysis. The thesis demonstrates how the constitution of a Swedish national identity in Northern Sweden constructed a dichotomy between an imagined civilized “Swedishness”, belonging to the future, and an imagined primitive Sámi Other, belonging to the past. It is argued that this discursive boundary work has not just situated some persons and their everyday life in a marginal position as a visible Sámi Other, but has also situated a substantial number of the inhabitants of Northern Sweden more or less in liminality and marginality in relation to the national identity structure. This has created a need for people to officially represent a more satisfactory collective identity, which includes a rewriting of the prehistory of the area. The last chapter relates the results to studies of similar cases in colonial and postcolonial contexts outside Europe. The essentialist view of identity and history present in several of the studied representations is also discussed. The thesis emphasizes the importance of a more nuanced view of relationships of ethnicity, domination and subordination, and the associated formation of collective memories, in Northern Sweden. Discourses of ethnicity and domination often function through simplifying dichotomies, but dichotomies alone cannot explain real conditions and consequences of these matters.